The theory of materials failure - Christensen, R. M. (Richard M.) (Oxford University Press, 2013)
A complete and comprehensive theory of failure is developed for homogeneous and isotropic materials. The full range of materials types are covered from very ductile metals to extremely brittle glasses and minerals. Two failure properties suffice to predict the general failure conditions under all states of stress. With this foundation to build upon, many other aspects of failure are also treated, such as extensions to anisotropic fiber composites, cumulative damage, creep and fatigue, and microscale and nanoscale approaches to failure.